Feeding and breeding management system of goat at central and southern regions of Bangladesh - Choudhury, Md Panir; Khatun, Anguara; Hossain, Md Shamsul; Islam, Farukul (Asian Journal of Medical and Biological Research, 2016)
Data were collected to study the feeding and breeding management system of goat from the villages of Mymensingh, Barguna and Patuakhali districts in Bangladesh through direct interviewing method using a pre-structured questionnaire. The research work was conducted from June to July 2014. Most of the goat rearing farmers in central and southern region of Bangladesh reared goats in semi-intensive system and kept their goats at goats house. Farmers took winter care and took bath of their goats during summer. Maximum farmers (82%) of central region supplied concentrate feed but 61% farmers of southern region did not supply concentrate to their goat. Farmers (82%) of central region provided particular feeder but 67.7% farmers of southern region did not provide feeder during concentrate feeding. Tube well (84%) was the main source of water of goat at central part of Bangladesh. But main sources of water in southern region were (46.3%) tube well and (51.2%) pond. All farmers of central region did not keep buck but only 19.5% farmers of southern region kept buck for breeding their female goat. Ninety two percent famers of central part of Bangladesh and 70.7% farmers of southern region used village buck for breeding their does. All buck keeping farmers at central region received service charge during breeding and they also practiced close breeding method. Most of (73.2%) the buck keeping farmers at southern region of Bangladesh received service charge of buck and they did not practice close breeding system. So, the present study might be suggested that farmers at central region were more careful of their goats in terms of feeds, feeding, water sources selection and watering but farmers at southern region were more aware about buck keeping and inbreeding depressions in their goats. Asian J. Med. Biol. Res. March 2016, 2(1): 9-12